2015
DOI: 10.1590/1982-0224-20140122
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salinity on survival, growth and biochemical parameters in juvenile Lebranch mullet Mugil liza (Perciformes: Mugilidae)

Abstract: Teleost fish growth may be improved under isosmotic condition. Growth and metabolic performance of juvenile Mugil liza (isosmotic point: 12‰) were evaluated after 40 days in different salinities (0, 6, 12 and 24‰). Tests were performed in quadruplicate (30 fish/tank; 0.48 ± 0.1 g body weight; 3.27 ± 0.1 cm total length) under controlled water temperature (28.2 ± 0.1°C) and oxygen content (>90% saturation). Fish were fed on artificial diet (50% crude protein) four times a day until apparent satiation. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
33
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 26 publications
6
33
0
2
Order By: Relevance
“…Also, it is important to note that juveniles of M. liza reared at 24‰ were shown to grow better than those maintained in fresh water for 40 days. However, fish reared at 12‰, which is very close to its isosmotic point (13.5‰), showed similar growth to those maintained at 0, 6 and 24‰ (Lisboa et al, 2015). Taken together, these findings clearly do not support the "Isosmotic Theory" for juveniles of the Lebranche mullet M. liza.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…Also, it is important to note that juveniles of M. liza reared at 24‰ were shown to grow better than those maintained in fresh water for 40 days. However, fish reared at 12‰, which is very close to its isosmotic point (13.5‰), showed similar growth to those maintained at 0, 6 and 24‰ (Lisboa et al, 2015). Taken together, these findings clearly do not support the "Isosmotic Theory" for juveniles of the Lebranche mullet M. liza.…”
mentioning
confidence: 64%
“…However, this theory seems to be species-specific, since it has been proved for some fish species like Sparus sarba (Woo & Kelly, 1995), but not for others like Paralichthys orbignyanus (Sampaio & Bianchini, 2002). Very recently, we have shown that juveniles of the Lebranche mullet M. liza reared at 12‰, a salinity close to the isosmotic point, did not display a better growth than those cultivated in a wide range of salinities (0-24‰) (Lisboa et al, 2015). Results from the present study are in agreement with this finding, thus suggesting that the idea of improving fish growth at isosmotic condition cannot be considered for juveniles of the Lebranche mullet M. liza.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Kondisi tambak BBRBLPP Gondol di musim kemarau, saat salinitas tinggi sangat memengaruhi pertumbuhan yang berkaitan dengan perangsangan makan maupun osmoregulasi. Menurut Lisboa et al (2015), sebagian besar hewan laut tipe osmoregulator-eurihalin, pengaruh langsung dari salinitas media pemeliharaan adalah melalui efek osmotiknya, ikan hanya akan mempertahankan keseimbangan terhadap Gambar 1. Pertumbuhan panjang total ikan bandeng, Chanos chanos dari lokasi perairan Aceh, Bali, dan Gorontalo.…”
Section: Pertumbuhan Dan Variasi Genetik Ikan Bandeng Chanos Chanos unclassified